Response to treatment with sodium stibogluconate for cutaneous leishmaniasis in indigenous and mestizo population, Amazonas, 2014-2018 - Huyhua-Gutierrez, Sonia Celedonia (2020)
Objetive. To determine the response to treatment with Sodium Stibogluconate in indigenous and mestizo population with diagnosis of cutaneous leishmaniasis according to treatment cycle, sex and life stage, belonging to the Microredes Nieva, Galilea, Tingo and Pedro Ruiz Gallo of the Amazon Region of 2014 - 2018, in Peru. Material and methods: Descriptive, retrospective, longitudinal-sectional study, having as sample universe 559 patient records; the method was inductive, technical data analysis and the instrument was the data record. Results: In the indigenous population, 98.1% responded to the treatment with the first cycle of Sodium Stibogluconate and in the mestizo population it was 94%, the other patients responded with the second treatment cycle; also of the total mestizo patients, 47.5% were female and 70.4% of the indigenous population were male (p=0,000); of the most affected life stages with the second cycle of treatment were the adult 50% (indigenous population) and in the child stage 11.2% (mestizo population). Conclusion: The highest percentage of the patients presented an adequate response (they cured with the first cycle of treatment) to Sodium Stibogluconate in both populations also the most affected life stages were adulthood and childhood